Justice In Absentia In Corruption Crimes - Ramadhan, Muhammad Alief (Corruptio, 2023)
Indonesian criminal law adheres to the criminal conviction system in absentia, namely the criminal conviction system in the absence of the Defendant. Justice in absentia is only allowed for traffic offenders. Then how is the judiciary in absentia applied in cases of corruption crimes. This research uses the empirical juridical method, which is an approach that examines secondary data first and then continues by conducting primary data research in the field. In the implementation of the judiciary by means of absentia in corruption cases, it has gone through the investigation stage where the summons against the Defendant is carried out three times, then the Public Prosecutor transfers the case to the Court not accompanied by the Minutes of Examination and Detention. In the examination process before the Court, the Panel of Judges has the authority to give a verdict on the reported criminal act. The Panel of Judges in deciding corruption crimes in absentia in the judgment Number: 8 / Pid.Sus-TPK / 2022 / PN. TJK and 9/Pid.Sus-TPK/2022/PN. TJK The defendant was found guilty of committing a criminal act of corruption by considering juridical, sociological, philosophical considerations.